The advantages of humanistic science learning tools - Sudarto Sudarto (SAINTIS Publishing, 2022)
This study aimed to determine the advantages of humanistic science learning tools. The collection data was cocducted by in-depth interviews and questionnaire. Data analysis techniques used namely: data reduction, data display, and conclusions drawing. The results of this study showed that the advantages of humanistic science learning tools were (1) making the teachers could teach Science easily, (2) providing high motivations to the teachers in teaching Science, (3) making the teachers more aware in developing the students' emotional, spiritual, and creativity potentials in Science learning, (4) Making the students felt happy to the Science learning, (5) Making the students more easier to understand the Science, (6) Motivating the students to learn Science, (7) Making the students more aware that the emotional, spiritual, and creativity potential had to be grown in science learning and (8) Opening students' horizons to develop their emotional, spiritual, and creative potential in their daily lives independently.